Characterization of refractory steel oxidation at high temperature. (March 2018) - Madern, Nicolas; Monnier, Judith; Baddour-Hadjean, Rita; Steckmeyer, Antonin; Joubert, Jean-Marc
Highlights: High temperature oxidation of two highly alloyed steels. Short terms oxidation kinetics measurements. Accurate characterization of oxidation products by combination of XRD, SEM-EDS and Raman spectroscopy. First report of manganese chromite spinel Raman signatures. Determination of the cation distribution and chemical formula of the mixed spinels, including the cation oxidation states. Abstract: The high temperature oxidation behavior of two highly alloyed refractory austenitic steels is studied at 1000 °C under air. Both short-term oxidation kinetics and long-term oxidation products are investigated. Structural, elemental and morphological analyses are coupled to characterize the oxide phases' formation. Chromia and spinel are the main phases for both samples although they suffer important descaling after 4 weeks oxidation, but alloying elements are responsible for the formation of many other oxides. Microstructures are compared and discussed. New Raman spectra are reported for manganese chromite spinels. Their assignments are provided and discussed at the light of the proposed cationic distribution.